Secret (extrait narratif du film D’ailleurs Derrida par Safaa Fathy): Тајна (наративен извадок од филмот Впрочем, Дерида од Сафа Фати) - Derrida, Jacques; Jovanovski, Zoran (Identities: Journal for Politics, Gender and Culture, 2004)
Author(s): Jacques Derrida | Жак Дерида Title (French): Secret (extrait narratif du film D’ailleurs Derrida par Safaa Fathy) Title (Macedonian): Тајна (наративен извадок од филмот Впрочем, Дерида од Сафа Фати) Translated by (French to Macedonian): Zoran Jovanovski | Зоран Јовановски Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 2 (Winter 2004) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 131-132 Page Count: 2 Citation (French): Jacques Derrida, “Secret (extrait narratif du film D’ailleurs Derrida par Safaa Fathy),” Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 2 (Winter 2004): Citation (Macedonian): Жак Дерида, „Тајна (наративен извадок од филмот Впрочем, Дерида од Сафа Фати)“, превод од француски Зоран Јовановски, Идентитети: списание за политика, род и култура, т. 3, бр. 2 (зима 2004): 131-132.